2013
DOI: 10.1002/jbm.a.34607
|View full text |Cite
|
Sign up to set email alerts
|

PEG2000‐DPSE‐coated quercetin nanoparticles remarkably enhanced anticancer effects through induced programed cell death on C6 glioma cells

Abstract: In this study, PEGylated nanoparticles quercetin drug delivery vehicles were investigated as carriers for anticancer drugs induced programed cell death (PCD). PEG2000-DPSE-coated quercetin nanoparticles were prepared and tumor cell killing efficacy was studied on glioma C6 cells and assayed for cell survival, apoptosis, or necrosis. The levels of ROS production and mitochondrial membrane potential (ΔΨm) were determined. Western blot assayed p53, p-p53, cytochrome C, and caspase proteins expression were also st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 37 publications
0
19
0
Order By: Relevance
“…Quercetin has been reported to have a role in prevention of diseases such as liver disease [12], pulmonary hypertension [13], and other cardiovascular diseases [14]. Furthermore, quercetin exhibits anti-inflammatory [15], anticancer [16], and antioxidant [17, 18] effects.…”
Section: Introductionmentioning
confidence: 99%
“…Quercetin has been reported to have a role in prevention of diseases such as liver disease [12], pulmonary hypertension [13], and other cardiovascular diseases [14]. Furthermore, quercetin exhibits anti-inflammatory [15], anticancer [16], and antioxidant [17, 18] effects.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study of ours ( 10 ), we reported that QUE/DSPE-PEG2000 showed significantly enhanced potency in glioma in vitro compared to free QUE. The aim of the present study was to evaluate the application of DSPE-PEG2000 as a nanocarrier for the combined delivery of QUE and TMZ for the treatment of glioma.…”
Section: Introductionmentioning
confidence: 65%
“…The development of clinically suitable liposome formulations has resulted from two major technological achievements: i) the inclusion of PEGylated lipids in the liposomes for the purposes of bypassing the reticuloendothelial system, resulting in significant drug accumulation in tumors ( 6 , 7 ); and ii) the strategic development of a remote drug-loading process based on the ammonium sulfate gradient method, to achieve significantly high quantities of drugs in the liposomes ( 8 ). We have previously demonstrated that the 1,2-distearoyl-sn-glycero-3-phosphoethanolamine-N-[methoxy(polyethylene glycol)-2000] (DSPE-PEG2000)-coated and quercetin (QUE)-loaded nanoliposomes (QUE-NLs) exhibited a hydrophilic layer on the surface, resulting in particle size increment, positive zeta ζ-potential, and enhanced physical stability ( 9 , 10 ). Notably, DSPE-PEG2000 coating of particles is a simple and flexible technology used to alter the surface properties of liposomes, and is expected to have broad applications in anticancer drug delivery systems.…”
Section: Introductionmentioning
confidence: 99%
“…In another study, high concentrations of quercetin were recorded in nanoliposomes on C6 glioma cells, which in turn induced a decrease of ∆Ψm, loss of adenosine triphosphate (ATP) and increased ROS production that together resulted in necrotic cell death, although lower concentrations of quercetin can induce apoptosis [38]. In a similar study, PEGylated nanoparticles of quercetin demonstrated dose-dependent cytotoxicity to C6 glioma cells and increase in the ROS levels, which led to the up-regulation of p53 protein and an increase in the cytochrome C and caspase-3 protein levels [39]. Conversely, increases in the caspase-3, 8 and 9 enzyme activities were identified in H 2 O 2 -treated C6 glioma cells and that were then blocked by the addition of quercetin, which resulted in the blocking of phosphorylated extracellular signal-regulated protein kinase (ERK) and p53 protein expressions induced by H 2 O 2 .…”
Section: Protective Effects Of Quercetin In Cns Tumorsmentioning
confidence: 92%
“…Human glioblastoma and rat glioma cell lines Reduced cell proliferation and increased antioxidant system [35,36,40] Rat glioma and human glioblastoma cell lines Induced cell death due to increased oxidative stress and activation of caspases [37][38][39]47,48] Glioblastoma cell lines Anti-inflammatory activity by inhibition of the STAT signaling pathway [45] Glioblastoma and astrocytoma cell lines In combination with other compounds induced apoptosis [49][50][51][52] Mouse model glioblastoma and cell line Induced autophagy by LC3-I processing and dose-dependency [47] Rat glioma model Increased tumor volume and reduced T lymphocyte infiltration and proliferation [58] Medulloblastoma cell lines and mouse model Decreased cell migration and growth tumor and increased survival [64,65]…”
Section: Type Of Study In Cns Tumor Effects Referencesmentioning
confidence: 99%